Tinjauan Yuridis Pembuktian Elektronik dalam Perkara Tindak Pidana Penipuan Online - Siregar, Zulkifli Anwar; Rafiqi, Rafiqi; Sitorus, Nanang Tomi (ARBITER: Jurnal Ilmiah Magister Hukum, 2024)
The purpose of this writing is to be able to review and analyze electronic information evidence of criminal acts of online fraud from the perspective of criminal procedural law in Indonesia.  The method used in this writing is to use a normative juridical method approach.  The problems discussed in this paper are how electronic evidence is used to prove criminal acts of fraud through online media and how electronic evidence is used for online fraud crimes based on Law no. 16 of 2019 concerning Amendments to Law no. 11 of 2008 concerning Information and electronic transactions, therefore the judge's task in his authority as a law enforcer is to interpret or interpret electronic evidence as an extension of documentary evidence or instructions which are valid evidence according to Article 184 of the Criminal Procedure Code, as regulated in Article 5 paragraphs (1) and (2) Law no. 16 of 2019 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions which regulates evidence, namely electronic information, electronic documents and printouts, as valid evidence and the expansion of evidence in criminal procedural law relating to acts criminal penalties regulated in the electronic information and transactions law.  Apart from that, to assist in interpreting and interpreting electronic evidence, judges need expert testimony in the evidentiary process. So, electronic information evidence is an extension of expert testimony and guidance evidence in accordance with Article 184 of the Criminal Procedure Code, expansion of legal evidence based on criminal procedural law. Furthermore, in Article 5 paragraph (3) of Law no. 16 of 2019 concerning Amendments to Law no. 11 of 2008 concerning Information and Electronic Transactions, through a negative legal proof system, that proof is not based only on legal regulations, but also on the judge's belief, so the judge also needs expert information to find out the real facts regarding electronic evidence, p. This relates to article 1 points 1 and 4 of Law no. 16 of 2019 concerning Amendments to Law number 11 of 2008 concerning Information and Electronic Transactions.